Lipid Profile and Insulin Resistance in Patients with Type-ΙΙ Diabetes Mellitus - Walid, Hadil; ali, Layla; Atiyah, majeed; Abdullah, awaz (Iraqi National Journal of Nursing Specialties, 2010)
Objective: To investigate the relation between dyslipidemia and insulin resistance where it is one of the metabolic disorders in patients with type-ΙΙ diabetes mellitus and compare the results with the control group. Methodology: Blood samples were collected from (35) patients with type-ΙΙ diabetes mellitus, besides (35) healthy individuals as a control group were enrolled in this study. The age of all subjects range from (20-50). Serum was used in determination of glucose, insulin, lipid profile (cholesterol (Ch), triglyceride (TG), high-density lipoprotein (HDL-Ch), low-density lipoprotein (LDL-Ch) and very low-density lipoprotein (VLDL), for patients and control groups. Insulin resistance (IR) was calculated according to homeostatic model (HOMA-IR). Results: The results revealed a statistically significant elevation levels (P<0.001) in each of glucose, insulin, insulin resistance, Ch, TG, LDL-Ch, and VLDL, except HDL-Ch which was decreased in all patients group comparing with control group. Recommendations: To study the Inflammatory factors and leptin and their relation to insulin resistance in type-ΙΙ DM.